Analisa Efisiensi Energi Algoritma Routing Low-Energy Adaptive Clustering Hierarchy (LEACH) Pada Wireless Sensor Network (WSN) Menggunakan MATLAB - Sari, Linna Oktaviana; Darbi, Ahmad; Rahayu, Yusnita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Wireless sensor networks (WSN) consists of a large number of sensor nodes. It has been pervasive in various applications including health care system, battlefield surveillance system, environment monitoring system and so on. The main issues of WSN is about how to extend lifetime by reducing power consumption of sensor nodes. Since the most energy is used for transmitting and receiving packet, and replacing batteries as a main power source of sensor nodes are impossible due the location of sensor nodes that is hazardous, routing protocol become the best solution for minimize power consumption of sensor nodes. Many routing protocols have been proposed to increase lifetime of WSN. One of these protocols called LEACH (Low Energy Adaptive Clustering Hierarchy). LEACH is the first clustering based routing protocol, many researcher proposed new protocols and compared it’s performance with LEACH. So, we decided to analyze LEACH using MATLAB. We found that LEACH can be more effective if more number of nodes in networks with the right number of cluster, more initial energy and if location of base station is near from the plan. Keywords : Wireless Sensor Networks, LEACH, Lifetime